Novas substâncias para malvaceas: Sida rhombifolia L. - Pereira, Fillipe de Oliveira (2012)
The use of medicinal plants dates back to ancient civilizations and are enough used for curing diseases. Brazil stands out in world for its high biodiversity in fauna and flora, within this found the family Malvaceae, which has the genus Sida as their third most important member, in species numbers. This genus is represented by 250 species worldwide, are enough utilized in Indian folk medicine, in Brazil is distributed throughout the national territory. Glimpsing contribute to the chemotaxonomy and pharmacological profile of the family Malvaceae, and based on the fact that Sida galheirensis showed excellent results in ago studies realized by team, was chosen an other species: Sida rhombifolia L. target of study of Msc.. The Phytochemical study of aerial parts of S. rhombifolia L. were isolated and identified ten substances: four steroids, four porphyrin, one flavonoid and one alkaloid.